SHEEP WELFARE MONITORING SYSTEM IN THE CONTEXT OF EUROPEAN STANDARDS - Antonik, Iryna; Zaruba, Kostiantyn; Nedosekov, Vitalii (Аграрний вісник Причорномор’я, 2026)
This article examines sheep welfare monitoring through a comparative analysis of the European Union regulatory framework and Ukraine’s evolving legal system. It draws on EU directives, regulations, scientific guidance, and strategic policy documents, alongside Ukrainian laws and subordinate acts introduced or updated in the course of harmonisation with European standards. Using comparative legal and content analysis, the study identifies the core components of welfare governance, the extent to which welfare requirements have been operationalised, and the main barriers to effective implementation. The analysis shows that the EU has developed a more operational welfare-monitoring model based on measurable animal- and resource-based indicators, risk-based official controls, traceability, and the growing use of digital tools across production, transport, and slaughter. Ukraine, by contrast, has made substantial legislative progress, particularly through Law No. 1206-IX and Law No. 4718-IX, but important implementation gaps remain. These include the insufficient specification of sheep-relevant biological and behavioural indicators, limited uptake of digital and sensor-based monitoring, weak integration of animal identification with welfare surveillance, and underdeveloped systems of staff training and certification. The study argues that convergence with European sheep welfare standards depends less on formal legal approximation alone than on the operationalisation of measurable welfare criteria, digital traceability, and implementation capacity. In this respect, the Ukrainian case is relevant beyond the national context for countries aligning livestock welfare governance with EU standards under conditions of agricultural transition, resource constraints, and post-war recovery